Ductal Carcinoma in situ of the breast in sclerosing adenosis encapsulated by a hamartoma: A case report. (2018) - Fukai, Shota; Yoshida, Atsushi; Akiyama, Futoshi; Tsunoda, Hiroko; Lefor, Alan Kawarai; Kimura, Jiro; Sakamoto, Takashi; Suzuki, Koyu; Mizokami, Ken
Highlights: Ductal Carcinoma in situ in sclerosing adenosis encapsulated by a hamartoma is rare. The diagnosis is difficult due to the appearance of these combined lesions. Atypical appearance of a hamartoma may suggest a co-existing malignancy. Abstract: Introduction: Ductal Carcinoma in situ (DCIS) of the breast can develop in areas of sclerosing adenosis. The radiographic finding of sclerosing adenosis is a spiculated mass and can look like invasive ductal carcinoma. We report a patient with DCIS in sclerosing adenosis encapsulated by a hamartoma, with imaging findings quite different from the typical findings of sclerosing adenosis. Presentation of case: A 73-year old woman, with no previous mammography, presented with a palpable mass in the left breast. Mammography showed a 36 mm well-defined mass with fat density in the middle outer quadrant of the left breast. Ultrasonography showed a well-defined mass in the same area which was composed of hypoechoic and hyperechoic areas. The histological diagnosis by core needle biopsy was sclerosing adenosis. We considered the patient's age and tumor size and performed a partial mastectomy for both diagnosis and treatment. Final pathology showed DCIS in sclerosing adenosis in a hamartoma. Discussion: This patient had DCIS in an area of sclerosing adenosis, encapsulated by a hamartoma. DCIS can develop in areas of sclerosing adenosis, and can appear similar to invasive ductal carcinoma, so we must avoid misdiagnosis or over-treatment. Malignant transformation of a hamartoma is rare, but can occur since it contains epithelial tissue. Definitive biopsy should be performed due to the possibility of a malignancy inside the hamartoma. Conclusions: When diagnosing a hamartoma, the presence of atypical findings on imaging studies, should suggest the possibility of malignancy. Although rare, a malignant tumor may be present inside the hamartoma.